Trait-mediated insect colonization of newly established grassland strips in agricultural landscapes - Maria Peer; Sophie Kratschmer; Raja Imran Hussain; Manuela Bürgler; Bea Maas; Dominik Rabl; Ronnie Walcher; Tobias Schernhammer; Norbert Schuller; Nora Vogel; Matthias Heer; Simon Zwatz; et al. (Basic and Applied Ecology)
Restoring grasslands in agroecosystems through the establishment of grassland and flowering strips has been demonstrated to promote insects. However, the development of the functional composition of insect assemblages in newly established grassland, which determine how species contribute to key ecosystem processes such as pollination, nutrient cycling, and pest control, are less understood. We applied a trait-based approach to investigate the functional insect richness of newly established grassland strips (NG) compared to adjacent permanent, semi-natural “old” grasslands (OG) over a six-year time span in an agricultural landscape in Austria. Specifically, our study focused on identifying species-specific traits that differentiate the assemblages of wild bees, syrphids, butterflies, orthopterans and heteropteran bugs in OG and NG. Our results show that compared to OG, insects in NG were more likely to be more mobile (butterflies, orthopterans, heteropteran bugs), less likely to be zoophagous (syrphids, orthopterans, heteropteran bugs), less likely to be feeding specialized (wild bees, orthopterans, heteropteran bugs) and less likely to be wood associated (butterflies). Investigating the temporal development of traits, our study reveals a shift in the abundance of zoophagous syrphids and mobile orthopterans following the establishment of NG: while we found lower numbers of zoophagous syrphids and mobile orthopterans in the first three years after the establishment of NG, this was no longer the case after five years.Our study suggests that although plant-diverse new grassland strips may exhibit equal taxonomic richness as permanent grasslands if created near the latter, they promote different functional compositions, even six years after establishment. Due to the lower initial occurrence of zoophagous insects following grassland establishment compared to permanent grassland, benefits for pest control could be delayed.